Systems thinking in sustainable agriculture development: a case study of garlic production in Indonesia - Puspitasari,; Nurmalina, Rita; Hariyadi,; Agustian, Adang (Frontiers in Sustainable Food Systems, 2024)
Sustainable agriculture involves intricate interactions among social, economic, and ecological dimensions, each with distinct interests and goals. Achieving sustainable agricultural development is complex, and demands a comprehensive response. Employing a system thinking approach, our study on Indonesia's garlic production seeks to provide a holistic understanding of the interconnected factors and relationships influencing sustainable agricultural systems, addressing the complexity of relationships among sustainability dimensions. We applied the first two steps of the five steps in developing systems thinking, that is, problem articulation and formulating dynamic hypotheses. Developing a causal loop diagram (CLD) as a representation of the dynamic hypothesis and identifying the system archetype that determines the system leverage and potential intervention points. The research highlights that the increase in garlic production is not solely attributed to the growth in planting area and productivity. Instead, it is closely linked to sustainable production factors, which result from the interaction of ecological, economic, and social variables. The underlying problem identified is the quantity and quality of garlic seeds. Therefore, government intervention can include the development of the seed industry through collaboration with research institutions. The ecological aspect involves providing environmentally friendly technological assistance and reducing dependence on chemical inputs. The sustainability of garlic production is highly dependent on farmers' interest in continuing to cultivate garlic, a decision rationalized by market and price certainty. Hence, the government should prioritize efforts to penetrate the local garlic market and consistently implement import restriction regulations.